2019
DOI: 10.22219/jpbi.v5i2.7193
|View full text |Cite
|
Sign up to set email alerts
|

Naturalist intelligence and personality: An understanding students’ responsible environmental behavior

Abstract: Notwithstanding that many efforts to overcome environmental problems have been carried out by several parties, yet the issues still occur. Improving students’ responsible environmental behavior (REB) can be an alternative to solve environmental problems. This study aimed to analyze the relation between the both variables (i.e. naturalist intelligence and personality) and students’ REB at SJHS 51 of Bandung. The research was carried out using quantitative descriptive method through a correlational approach. Nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
0
7
1
3
Order By: Relevance
“…Furthermore, the interaction between PBL and NI had no effect on the students' UEC. However, the finding is different from the results of the study by Wirdianti, Komala, & Miarsyah (2019) According to them, there is a relationship between NI and students' pro-environmental behavior (PEB). Although the variables studied are related to the psychomotor domain, but PEB and UEC have links to environmental knowledge (Duan & Sheng, 2018;Zheng et al, 2018).…”
Section: Resultscontrasting
confidence: 75%
“…Furthermore, the interaction between PBL and NI had no effect on the students' UEC. However, the finding is different from the results of the study by Wirdianti, Komala, & Miarsyah (2019) According to them, there is a relationship between NI and students' pro-environmental behavior (PEB). Although the variables studied are related to the psychomotor domain, but PEB and UEC have links to environmental knowledge (Duan & Sheng, 2018;Zheng et al, 2018).…”
Section: Resultscontrasting
confidence: 75%
“…Moreover, the study of Wirdianti et al (2019) on natural intelligence and personality found a relation between naturalist intelligence and responsible environmental behavior. Therefore, boosting both competencies is necessary for enhancing students' green initiatives.…”
Section: Multiple Intelligencesmentioning
confidence: 99%
“…(Lualhati, 2019) 11 Peran tanggung jawab pribadi penting untuk menumbuhkan niat pro lingkungan yang dapat mengubah perilaku pro lingkungan siswa (Dasi et al, 2019) 12 Peningkatan perilaku lingkungan yang bertanggung jawab siswa dapat menjadi salah satu alternatif pemecahan masalah lingkungan. (Wirdianti et al, 2019) 13 Tanggung jawab lingkungan merupakan aspek penting yang menentukan pemecahan masalah lingkungan dalam rangka meningkatkan perilaku pro lingkungan. (Sigit et al, 2019) 14 Literasi lingkungan diindikasikan sebagai salah satu unsur pembelajaran yang mampu memecahkan masalah lingkungan.…”
Section: Kata Kunci Yang Sering Digunakanunclassified